N [epsilon] -(carboxymethyl)lysine-receptor for advanced glycation end product axis is a key modulator of obesity-induced dDysregulation of adipokine expression and insulin resistance - Gaens, Katrien; Goossens, Gijs H.; Niessen, Petra M.; van Greevenbroek, Marleen M.; van der Kallen, Carla J.H.; Niessen, Hans W.; Rensen, Sander S.; Buurman, Wim A.; Greve, Jan Willem M.; Blaak, Ellen E.; van Zandvoort, Marc A.; Bierhaus, Angelika; et al. (Arteriosclerosis, thrombosis, and vascular biology, 2014)
Objective—Dysregulation of inflammatory adipokines by the adipose tissue plays an important role in obesity-associated insulin resistance. Pathways leading to this dysregulation remain largely unknown. We hypothesized that the receptor for advanced glycation end products (RAGE) and the ligand Nε-(carboxymethyl)lysine (CML) are increased in adipose tissue and, moreover, that activation of the CML-RAGE axis plays an important role in obesity-associated inflammation and insulin resistance.Approach and Results—In this study, we observed a strong CML accumulation and increased expression of RAGE in adipose tissue in obesity. We confirmed in cultured human preadipocytes that adipogenesis is associated with increased levels of CML and RAGE. Moreover, CML induced a dysregulation of inflammatory adipokines in adipocytes via a RAGE-dependent pathway. To test the role of RAGE in obesity-associated inflammation further, we constructed an obese mouse model that is deficient for RAGE (ie, RAGE-/-/LeptrDb-/- mice). RAGE-/-/LeptrDb-/- mice displayed an improved inflammatory profile and glucose homeostasis when compared with RAGE+/+/LeptrDb-/- mice. In addition, CML was trapped in adipose tissue in RAGE+/+/LeptrDb-/- mice but not in RAGE-/-/LeptrDb-/-. RAGE-mediated trapping in adipose tissue provides a mechanism underlying CML accumulation in adipose tissue and explaining decreased CML plasma levels in obese subjects. Decreased CML plasma levels in obese individuals were strongly associated with insulin resistance.Conclusions—RAGE-mediated CML accumulation in adipose tissue and the activation of the CML-RAGE axis are important mechanisms involved in the dysregulation of adipokines in obesity, thereby contributing to the development of obesity-associated insulin resistance.
Im Titel ist "epsilon" als griechischer Buchstabe dargestellt und hochgestellt
Gesehen am 20.08.2020